Evaluation of the Mayo Additive Staging System in patients with newly diagnosed multiple myeloma: A real‐world analysis. (23rd November 2022) - Chen, Haimin; Shi, Haotian; Zhou, Nian; Yu, Wenjun; Wu, Lixia; Peng, Rong; Wei, Wei; Wang, Dongjiao; Zhou, Fan
Abstract: Objectives: Recently, the Mayo Clinic introduced a new staging system (the Mayo Additive Staging System [MASS]) for patients with newly diagnosed multiple myeloma (NDMM) based on the number of high‐risk (HR) abnormalities, including HR IgH translocations, 1q gain/amplification, chromosome 17 abnormalities, International Staging System (ISS)‐III, and elevated lactate dehydrogenase. Patients with 0, 1, or ≥2 HR abnormalities were defined as stage I, II, or III, respectively. We aimed to validate the real‐world prognostic value of the MASS. Methods: We retrospectively analyzed the cytogenetic and laboratory results of 544 patients with NDMM at a single center. Results: Ninety (16.5%) patients had no HR factors (MASS I), 193 (35.5%) had 1 HR factor (MASS II), and 261 (48%) had ≥2 HR factors (MASS III). The median progression‐free survival (PFS) and overall survival (OS) times were 48, 28, and 20 months and 137, 73, and 39 months in the three groups, respectively ( p < .001). In the subgroup analysis, patients had different OS outcomes based on the MASS when grouped by age, renal function, or therapeutic regimens. The MASS identified patients with the worst outcomes among those rated revised ISS II. Conclusion: The MASS system is a reliable risk stratification tool for patients with NDMM in real‐world clinical practice.